Is there a place for women in the theology of the Psalms? Part I: an investigation of the female imagery of the ancient Hebrew Psalter - Efthimiadis-Keith, Helen (Old Testament Essays, 1999)
This article examines the place of women in the theology of the Psalms, an area of research with very few, if any, substantial contributions (cf Introduction, A). As such, the article surveys the different types of female imagery occurring in the Psalms(mundane, divine, personified, mythological and absent female imagery, B, a and b) and evaluates them according to their positive, negative, ambivalent and/or neutral value for modern Western women. The article ends with a summary of the investigation results and a preliminary conclusion regarding the question posed as its title (C).
free
Keywords: Christianity; Psalms; Women in the Bible; Women in the Old Testament